O sentido do psicodrama na clínica fonoaudiológica - Lima, Priscila Saraiva (2005)
The goal of this research is to understand the role of Psychodrama in a speech therapy clinic in order to reflect on the possibilities of the psychodramatic approach and its techniques in the context of the clinical-therapeutical work in Speech Therapy. In order to do that, we conducted four semi-structured interviews with speech therapists working in the clinic for at least three years and using Psychodrama. The method we adopted for the discourse analysis is based on Bardin s proposal (1994), which refers to content analysis, and the technique used was the category analysis. Based on the interview presentation and analysis, we tried to select, among the categories found, discourse that had information about the psychodramatic approach and its techniques being used in the speech therapy clinic. The first aspect noticed in the discourse analyzed is that the psychodramatic approach serves as a means to bring the subject closer to the speech therapy work, promoting therapist-patient bond and generating changes in the subjectivity. A second aspect noticed in the discourse was that the interviewees divided Psychodrama into Psychotherapic and Pedagogical or Educational. Thus, throughout the research and based on our interviewees discourse, it was clear that the speech therapy clinic supported by psychodramatic techniques is in line with the psychotherapic approach of Psychodrama, making for speech therapy work within the clinic contextualized approach